2003
DOI: 10.2519/jospt.2003.33.9.492
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Neuromuscular Electrical Stimulation Protocol for Quadriceps Strength Training Following Anterior Cruciate Ligament Reconstruction

Abstract: Study Design: Randomized clinical trial, single-masked. Objectives: To determine the effectiveness of using a modified neuromuscular electrical stimulation (NMES) training program as an adjunct treatment for improving quadriceps strength and physical function in rehabilitation following anterior cruciate ligament reconstruction (ACLR). Background: NMES training for quadriceps strengthening has previously been shown to be an effective adjunct treatment following ACLR when performed against isometric resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
150
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(155 citation statements)
references
References 21 publications
1
150
1
3
Order By: Relevance
“…None of the studies described concealment of allocation at the time of randomization. Among the studies with drop outs, [13][14][15]21,22 only Fitzgerald et al 15 mentioned intentionto-treat analysis. The baseline participant characteristics were well described and the groups were comparable.…”
Section: Methodsological Quality Of the Studies Included (Table 4)mentioning
confidence: 99%
See 3 more Smart Citations
“…None of the studies described concealment of allocation at the time of randomization. Among the studies with drop outs, [13][14][15]21,22 only Fitzgerald et al 15 mentioned intentionto-treat analysis. The baseline participant characteristics were well described and the groups were comparable.…”
Section: Methodsological Quality Of the Studies Included (Table 4)mentioning
confidence: 99%
“…Blinded outcome assessment was reported in four studies. 15,21,23,24 None of the studies included reported sample size calculations.…”
Section: Methodsological Quality Of the Studies Included (Table 4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Emphasis is placed on ability to produce a full sustained contraction of the quadriceps muscle. Several trials have demonstrated the benefits of high intensity electrical stimulation to improve quadriceps strength and gait parameters [3,4,[59][60][61][62][63][64]. It is not uncommon for patients to have poor quadriceps tone during the first postoperative visit.…”
Section: Introductionmentioning
confidence: 99%